Inner ear MRI enhancement based on three dimensional‐real IR sequence in patients with Meniere's disease after intravenous gadolinium injection: Comparison of different doses used and exploration of an appropriate dose. (23rd January 2022) - Chen, Wei; Geng, Yue; Niu, Yue; Lin, Naier; Wang, Xiaolin; Sha, Yan
Abstract: Objectives: Three‐dimensional inversion‐recovery sequence with real reconstruction (3D‐real IR) magnetic resonance imaging (MRI) can detect endolymphatic hydrops of the inner ear. We aimed to explore a appropriate dose for intravenous gadolinium injection. Design: Observational prospective study. Setting: Tertiary referral centre. Participants: We collected 90 unilateral definite Meniere's disease patients. Main outcome measures: All enrolled patients were divided into three groups randomly (patients in group A, B and C received gadolinium injection in 1/1.5/2 times doses respectively). After 4 h, inner ear MRI scans were applied. Results: The signal intensities of B‐affected ears and C‐affected ears were significantly higher than A‐affected ears ( p  < .05); however, no difference was found between B‐affected ears and C‐affected ears ( p  = .267). The same conditions also appeared in the three unaffected‐ear groups. Moreover, the signal intensities of affected‐ear in group A, B and C were significantly higher than that of the corresponding unaffected‐ear groups ( p  < .05). Besides, the subjective visual evaluation scores of group B and C were significantly better than that of group A ( p  < .05). Conclusions: Intravenous injection of gadolinium in a single dose may be unbefitting for the inner ear imaging based on 3D‐real IR MRI, both the applications of gadolinium in 1.5 times and double doses can have a good perilymphatic enhancement effect of inner ear. In order to minimise the use of dose for avoiding or mitigating the adverse reactions and renal damage, 1.5 times dose may be preferred in clinical practice.